Textbook of Environmental Disaster Management - Thakur D K (Jaipur Manisha Prakashan, 2014)
Natural Hazards and Disasters: Management for Sustainable Development; Role of Remote Sensing and GIS Technology; Major Indian Earthquakes Its Impact on Indian Economy; Developing an Asian Tsunami Warning System; Disaster Management in India; Application of Remote Sensing and GIS to water Resources Management; Role of Vegetation -Argo System to Check Natural Hazards in the Mountains.